Applying event classification to reveal the Estado da Índia - Albuquerque, Gonçalo (2024)
This paper presents a study based on the application of a Portuguese event detection (extraction and classification) tool (TEFE) to historical texts. It shows how historical analysis and interpretation can use this tool in historical research, on the basis of a historiography analysis of the Portuguese Empire in East. TEFE has been applied to one volume of the Portuguese Livros das Monções (Monsoon Books), concerning the time gap between 1614 and 1616, highlighting conflict-related categories of events. A historical analysis of this special category of events is performed, revealing aspects of a generalized juncture of war and conflict in Asia in the early seventeenth century.